2010
DOI: 10.1016/j.chemosphere.2010.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous ozonation of suspended malathion and chlorpyrifos particles

Abstract: a b s t r a c tThe heterogeneous ozonation of suspended malathion and chlorpyrifos particles are studied in real-time with a vacuum ultraviolet photoionization aerosol time-of-flight mass spectrometer (VUV-ATOFMS). The pesticide particles with the diameter of hundreds of nanometers are generated by the homogeneous nucleation method using azelaic acid as nucleus. The reactions are carried out in an aerosol reaction chamber under ambient pressure (1 atm) and room temperature (298 K), respectively. The time-of-fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 44 publications
(63 reference statements)
5
15
0
Order By: Relevance
“…The PIII and PIV are also observed in the reaction between chlorpyrifos-methyl with OH radicals [38]. The proposed formation mechanism of the disulfide compound is in accordance with the previous reports on the phosphinyl disulfides formed from thiols [33,37,40]. The similar disulfide compounds have also been observed in the heterogeneous reaction of suspended malathion particles with NO 3 radicals and ozone in previous studies [33,41].…”
Section: Reaction Pathwayssupporting
confidence: 78%
See 3 more Smart Citations
“…The PIII and PIV are also observed in the reaction between chlorpyrifos-methyl with OH radicals [38]. The proposed formation mechanism of the disulfide compound is in accordance with the previous reports on the phosphinyl disulfides formed from thiols [33,37,40]. The similar disulfide compounds have also been observed in the heterogeneous reaction of suspended malathion particles with NO 3 radicals and ozone in previous studies [33,41].…”
Section: Reaction Pathwayssupporting
confidence: 78%
“…The proposed formation mechanism of the disulfide compound is in accordance with the previous reports on the phosphinyl disulfides formed from thiols [33,37,40]. The similar disulfide compounds have also been observed in the heterogeneous reaction of suspended malathion particles with NO 3 radicals and ozone in previous studies [33,41]. Some differences are found between the proposed pathways in this study and those of chlorpyrifos in aqueous solution by ultrasonic irradiation and in a cranberry bog by soil microorganism [10,19].…”
Section: Reaction Pathwayssupporting
confidence: 77%
See 2 more Smart Citations
“…4 In the previous studies, the heterogeneous reaction rates of pesticides with O 3 were reported to be in the order of $10 À18 cm 3 molecule À1 s À1 . 42,43 Compared to the results obtained in this study, the effective rate constant of ametryn with NO 3 radicals was $5 orders of magnitude faster than those of particulate pesticides with O 3 . Compared with NO 3 radicals, the effect of OH radicals on the degradation of atmospheric particulate organic compounds may not be remarkable due to its lower concentration in the atmosphere.…”
Section: Heterogeneous Kineticsmentioning
confidence: 82%